Neoliberalizm i jego (nie)etyczne implikacje edukacyjne - Michałowska, Danuta Anna (Wydawnictwo Naukowe UAM, 2013)
Głównym celem książki jest analiza dyskursu neoliberalnego we współczesnym świecie i jego wpływu na politykę oświatową, ze szczególnym uwzględnieniem edukacji etycznej i problemów wychowania. Jest to krytyczna analiza projektu etycznego i globalnej ekspansji neoliberalizmu jako doktryny ekonomicznej, politycznej i etycznej. Książka ma trzy części: 1. „Neoliberalizm i jego wartości rzekome” – jest to analiza wartości w doktrynie neoliberalnej; 2. „(Anty)edukacyjne konsekwencje neoliberalizmu” - ukazanie edukacyjnych konsekwencji praktyki systemu neoliberalnej ekonomii i polityki oraz 3. „Krytyka neoliberalnej edukacji etycznej – w poszukiwaniu alternatywy” - relacje edukacji etycznej i polityki neoliberalnej. W efekcie krytycznej analizy dyskursu neoliberalnego zostały ukazanie (nie)etyczne konsekwencje tej ideologii, z drugiej strony została podjęta próba znalezienia innych bardziej korzystnych rozwiązań edukacyjnych dla rozwoju jednostki i społeczeństwa.

The main aim of this book is to analyze the neoliberal discourse in today’s world and the influence it has on the educational policy, especially on ethical education, as well as teaching and upbringing issues. This is a critical analysis of the ethical project and global expansion of neoliberalism as an economic, political and ethical doctrine. This book has three parts: 1. “Neoliberalism and its supposed values” – this is a critical analysis of neoliberal values; 2. “The (anti-)educational consequences of neoliberalism” – this part presents the negative educational consequences of neoliberal economy and politics; 3. “A criticism of neoliberal ethical education – in search of an alternative” – this is an attempt to describe and understand the relations between ethical education and neoliberal politics. As a result of a critical discourse analysis of neoliberalism, (un)ethical consequences of this ideology were shown.Also, an attempt was made to find alternative educational solutions, especially in the field of ethical education, that would be more favorable for the development of individuals and the society.
Neoliberalism and (non)ethical implications for education
Neoliberalizm i jego (nie)etyczne implikacje edukacyjne (2013) stanowi próbę dokonania analizy etycznych aspektów neoliberalizmu i kształtu neoliberalnego projektu edukacji. Zastosowanie Krytycznej Analizy Dyskursu (KAD) umożliwiło pokazanie konsekwencji neoliberalizmu we współczesnym świecie i jego wpływu na politykę edukacyjną, zwłaszcza na edukację etyczną, sferę wartości, proces nauczania i wychowania. This book presents reflections and analyses regarding the ethical aspects of neoliberalism and the project of neoliberal education. The author used the theory of Critical Discourse Analysis (CDA) to show the consequences of neoliberalism in today’s. The conclusions derived from this analysis provide a new perspective on the structure and quality of education and especially on the cognitive and ethical development of young people and also their value system. The ethical problems related to neoliberalism occur in contemporary educational policy both in Poland and in other countries too often. However, the results of the research show that most people seem to be unaware of them. This situation and the power of neoliberal discourse pose a threat to democratic, ethical education. Neoliberal discourse and its educational implications create a specific vision of what makes us unique as humans. Homo neoliberalis, who is a combination of homo oeconomicus and homo consumans, is this neoliberal discourse’s product.The second and the third part of this book present the results of the author’s own research. They show the preferred values of 69 Polish teachers. Some of these values are promoted in neoliberal discourse. There is a need to present the main topic of this monograph from an interdisciplinary point of view (educational, sociological, axiological, philosophical and political, economic, psychological and cognitive). This perspective makes it possible to create a new picture of school reality with regard to ethical education and the teachers’ everyday practices, which allows one to foresee and plan educational strategies.
Keywords: neoliberalizm, edukacja, wartości; polityka oświatowa, edukacja etyczna; neoliberalism, education, values; educational politics, ethics in education, ethical education; socjologia edukacji; educational sociology